IMPLIKASI PROSES HUKUM YANG ADIL TERHADAP KELOMPOK KRIMINAL BERSENJATA DAN REKOMENDASI KESEJAHTERAAN SOSIAL DI PAPUA - Achmad Yusuf; Otti Ilham Khair; Gede Wijaya Kusuma; Muhammad Nasruddin (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
Abstract This study aims to implicate a fair legal process against armed criminal groups and social welfare recommendations in Papua. In order to carry out a better, systematic and directed study in accordance with the expected goals, this writing is based on the results of research or legal studies. The results of this study are in the form of an acronym for the Armed Criminal Group, which is a group that often spreads terror against both civilians and the TNI and Polri in the Papua region. The aim of the KKB Papua is to break away from the Unitary State of the Republic of Indonesia (NKRI). Therefore, the Papuan KKB can be called a separatist movement, whose movements often result in fatalities. Before being born as KKB, this group was formerly known as the Free Papua Organization (OPM) and a fair trial or fair trial is a principle which is an indicator of the development of a just society and legal system. Without the application of fair trial principles, many innocent people will enter the criminal justice system and will most likely end up in jail. Without the application of fair trial principles, law and public trust in law and the justice system will collapse.